Does Industrial Relations Research Support Policy? A Comparative Assessment of Research on Spain - Rohlfer, Sylvia (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2013)
This article reviews the English-speaking literature on Spanish and German industrial relations published in the top 10 journals in this field between 2000 and 2010. The analysis contributes to the ongoing debate about the relevance of industrial relations by establishing the state of the art in research on Spain in comparison to Germany. Following this assessment we then ask whether existing research on Spain is well situated to orient policymakers. The consequences of either normative or normative-free research have largely been overlooked; our discussion expands on two contrasting positions: suggesting a move away from ideology in research (Mitchell, 2001) or recommending normative assumptions as a necessary precondition (Frege, 2007) in the context of Spain.Our findings reveal a greater convergence in research regarding its restricted multidisciplinary character, its focus on the international level and a strong emphasis on empirical, quantitative work with analysis conducted at various levels. At the same time, some path dependency continues to exist, particularly concerning the active participants in research and the subjects for investigation. The results point to deficiencies in research on Spanish industrial relations. We conclude by advocating an openly stated, normative base in industrial relations research to guide policymakers in Spain. While an evidence-based approach in policy making is desirable, normative choices are highly consequential and should feature in research in order to avoid a “democratic shock” in Spain.